2013
DOI: 10.1007/s13644-013-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Image of God and Community Volunteering among Religious Adherents in the United States

Abstract: Individual theological beliefs provide important motivations for religious people to volunteer in their communities. Compassion and loving one's neighbor are both ideas that can motivate individuals to volunteer their time and talents. Religious believers who have conservative theological beliefs may see volunteering for their communities as a minor factor in their religious calling. Recent research on the role of social embeddedness within religious communities, however, has questioned the importance of theol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
1
34
0
2
Order By: Relevance
“…Indeed, what one believes about God has been shown to predict a wide range of social and moral attitudes, including gender equality (Whitehead ), the value of volunteering (Mencken and Fitz ), political tolerance (Froese, Bader, and Smith ), trust of others (Hinze, Mencken, and Tolbert ; Mencken, Bader, and Embry ), social conservatism (Froese and Bader ), environmentalism (Greeley ), distributive justice (Froese and Bader ), xenophobia (Rowatt et al. ), and, notably, punitive attitudes (Applegate et al.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, what one believes about God has been shown to predict a wide range of social and moral attitudes, including gender equality (Whitehead ), the value of volunteering (Mencken and Fitz ), political tolerance (Froese, Bader, and Smith ), trust of others (Hinze, Mencken, and Tolbert ; Mencken, Bader, and Embry ), social conservatism (Froese and Bader ), environmentalism (Greeley ), distributive justice (Froese and Bader ), xenophobia (Rowatt et al. ), and, notably, punitive attitudes (Applegate et al.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from previous research on religion and social and political trust and confidence are mixed. Some scholars maintain that religious participation can, in certain cases, increase social trust (Mencken & Fitz, 2013;Welch et al, 2004). Mencken and Fitz (2013) state that religious participation can build trust in the community, which encourages volunteering and helping others.…”
Section: Religion and Institutional Confidencementioning
confidence: 99%
“…Some scholars maintain that religious participation can, in certain cases, increase social trust (Mencken & Fitz, 2013;Welch et al, 2004). Mencken and Fitz (2013) state that religious participation can build trust in the community, which encourages volunteering and helping others. Welch et al (2004) show mixed results regarding the relationship between religious affiliation and trust, but found that Pentecostals who are frequent participants have higher levels of trust.…”
Section: Religion and Institutional Confidencementioning
confidence: 99%
See 2 more Smart Citations